2016
DOI: 10.4088/jcp.15m10617
|View full text |Cite
|
Sign up to set email alerts
|

Incident Psychosis in Subjects With Mild Cognitive Impairment or Alzheimer’s Disease

Abstract: Objective To estimate the incidence of psychotic symptoms in Alzheimer disease. Methods The study consists of 776 elderly subjects presenting to the Alzheimer Disease Research Center at the University of Pittsburgh between May 9, 2000 and August 19, 2014. All participants were diagnosed with mild cognitive impairment (National Institute on Aging-Alzheimer’s Association workgroup criteria), possible, or probable Alzheimer disease (National Institute of Neurologic and Communicative Disorders and Stroke and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…Consistent with these observations, we recently estimated the annual incidence of psychosis in AD subjects at ~10% (Weamer et al, 2016). The most rapid increase in rates of psychosis in AD is in the transition from mild cognitive impairment to early and middle stages of disease, with a plateau in later stages (Lopez et al, 2003; Ropacki and Jeste, 2005; Weamer et al, 2016). When present, psychotic behaviors in AD have an adverse impact on the patient and family.…”
Section: Introductionsupporting
confidence: 54%
“…Consistent with these observations, we recently estimated the annual incidence of psychosis in AD subjects at ~10% (Weamer et al, 2016). The most rapid increase in rates of psychosis in AD is in the transition from mild cognitive impairment to early and middle stages of disease, with a plateau in later stages (Lopez et al, 2003; Ropacki and Jeste, 2005; Weamer et al, 2016). When present, psychotic behaviors in AD have an adverse impact on the patient and family.…”
Section: Introductionsupporting
confidence: 54%
“…We recently estimated the annual incidence of psychosis in AD at 10%. 40 Thus there is an opportunity to intervene prior to psychosis onset if individual predictors can be identified. Although currently no treatments are established for prevention of AD+P, selective serotonin reuptake inhibitors have some efficacy for treating it, 22 ; 23 and they have acceptable tolerability.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, subjects with a primary diagnosis of Dementia with Lewy bodies 38 were excluded. The above diagnoses resulted from diagnostic evaluations, cognitive testing, and in some cases neuropathologic assessment, conducted during subjects’ participation in the following programs as previously described: the University of Pittsburgh Alzheimer Disease Research Center (ADRC), 39 ; 40 the Genetic and Environmental Risk in AD Consortium 1 (UK), 29 ; 41 ; 42 the National Institute on Aging’s Late Onset Alzheimer’s Disease Family Study (NIA-LOAD), 4 ; 28 the National Institute of Mental Health Genetics Initiative AD Cohort (NIMH), 25 the Fundació ACE Barcelona Alzheimer Treatment and Research Center (ACE), 41 ; 43 , the Cardiovascular Health Study (CHS), 3 ; 41 and a consortium of National Institute on Aging Alzheimer Disease Centers (ADC). 44 Collection of clinical data and genetic samples were approved by each sites local Institutional Review Board or Medical Ethics Committee, as appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…As well, psychosis is a common feature in AD, estimated to occur in as many as 50% of patients [23] . Recent studies have suggested in fact an incidence rate of 10% per year [24] . Thus, it is possible that the high prevalence of psychosis in AD may partially explain the observed findings.…”
Section: Discussionmentioning
confidence: 99%